Dietary intake and growth in children with Prader–Willi syndrome. Issue 5 (9th April 2021) - Meade, Christina; Martin, Ruth; McCrann, Ann; Lyons, Jacqueline; Roche, Edna
Abstract: Background: The management of Prader–Willi Syndrome (PWS) requires strict dietary supervision to prevent obesity, avoid micronutrient deficiencies and ensure optimal growth. The present study aimed to examine the growth and dietary intake of children with PWS. Methods: All children with genetically confirmed PWS attending Children's Health Ireland (CHI) at Tallaght ( n  = 44) were invited to participate. Anthropometry was performed and body composition measured using bioelectrical impedance analysis. Three‐day food diaries were used to evaluate dietary intake and the presence of early feeding issues was assessed. Serum haemoglobin, ferritin and vitamin D levels were measured. Results: Nineteen children participated, with a mean (range) age of 7.6 (0.6–18.1) years. Most were female ( n  = 14, 74%). Twenty‐percent ( n  = 3) were underweight, 60% ( n  = 9) were healthy weight, n  = 1 was overweight and n  = 2 were obese. Mean (range) percentage body fat was 25.7% (10%–40%). Eigthy‐three percent reported early feeding issues. Ninety‐four percent ( n  = 16) achieved ≤ 100% of estimated average requirement (EAR) for energy. Mean daily energy intake for ≤ 5 years old was 722 kcal (9 kcal cm –1 /72–112% EAR); for those ≥ 12 years, it was 1203 kcal (8.3 kcal cm –1 /41%–82% EAR). Suboptimal calcium, vitamin D, iron, zinc and fibre intake was evident. Iron deficiency anaemia and vitamin D insufficiency occurred in two children. Conclusions: The present study provides the first Irish data for PWS and shows that energy intake does not appear to be excessive, with four in five patients being underweight or of a normal BMI. Suboptimal dietary intake of several micronutrients was evident and biochemical nutrient deficiencies were present. Abstract : The present study examines dietary intake and growth in Prader–Willi syndrome (PWS). It highlights the presence of early feeding difficulties in infancy. It also details the degree of dietary restriction necessary to avoid overweight and obesity in children with PWS and draws attention to the risk of micronutrient deficiencies in this population.